Small Airway Dysfunction in Chronic Bronchitis with Preserved Pulmonary Function - Qi Ding; Bai-Bing Mi; Xia Wei; Jie Li; Jiu-Yun Mi; Jing-Ting Ren; Rui-Li Li (Canadian Respiratory Journal)
Impairment of pulmonary function was evaluated in chronic bronchitis patients with preserved ratio impaired spirometry (PRISm). We retrospectively collected clinical data from 157 chronic bronchitis (CB) and 186 chronic obstructive pulmonary disease (COPD) patients between October 2014 and September 2017. These patients were assigned to three groups: control (normal pulmonary function), PRISm (forced expiratory volume in 1 second [FEV1]/forced vital capacity [FVC] ≥ 0.7, FEV1 < 80% of predicted value), and COPD (FEV1/FVC <0.7) groups. Because small airway function was the main focus, in the COPD group, only patients in accordance with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades 1 and 2 were included. Evaluation of pulmonary function (including impulse oscillometry) was performed and compared among these groups. Compared with the control group, the PRISm and COPD groups showed statistically significant differences in the predicted FEV1% p<0.001, maximal expiratory flow (MEF) 25% p<0.001, MEF50% p<0.001, maximal midexpiratory flow (MMEF) 25–75% p<0.001, residual volume (RV)/total lung capacity (TLC; p<0.001), FVC% p<0.001, total respiratory resistance and proximal respiratory resistance (R5-R20; p<0.001), respiratory system reactance at 5 Hz (X5; p<0.001), resonant frequency (Fres; p<0.001), and area of reactance (Ax; p<0.001). However, the predicted FEV1% and RV/TLC were similar between the PRISm and COPD groups (p=0.992 and 0.122, respectively). PRISm is a nonspecific pattern of pulmonary function that indicates small airway dysfunction and may increase the risk of transformation to obstructive ventilation dysfunction. This trial is registered with ChiCTR-OCH-14004904.